Advances in the diversity knowledge of Brassicaceae family in Ancash, Peru - Monsalve, Christhian (2005)
The presence of 40 species of plants of the Brassicaceae family grouped in 17 genera and 5 tribes is confirmed within the area of study . From the total of the species, three are considered endemic of Ancash and two are nationally endemics. Dichotomous keys for the genera and species are presented as well as distribution information for each of the species.